Intermetallic Nanocrystals: Syntheses and Catalytic Applications. Issue 14 (24th February 2017) - Yan, Yucong; Du, Jingshan S.; Gilroy, Kyle D.; Yang, Deren; Xia, Younan; Zhang, Hui
Abstract : At the forefront of nanochemistry, there exists a research endeavor centered around intermetallic nanocrystals, which are unique in terms of long‐range atomic ordering, well‐defined stoichiometry, and controlled crystal structure. In contrast to alloy nanocrystals with no elemental ordering, it is challenging to synthesize intermetallic nanocrystals with a tight control over their size and shape. Here, recent progress in the synthesis of intermetallic nanocrystals with controllable sizes and well‐defined shapes is highlighted. A simple analysis and some insights key to the selection of experimental conditions for generating intermetallic nanocrystals are presented, followed by examples to highlight the viable use of intermetallic nanocrystals as electrocatalysts or catalysts for various reactions, with a focus on the enhanced performance relative to their alloy counterparts that lack elemental ordering. Within the conclusion, perspectives on future developments in the context of synthetic control, structure–property relationships, and applications are discussed. Abstract : Intermetallic nanocrystals are superior catalysts over their alloy counterparts with the same composition but a disordered atomic structure. An account of recent progress in the development of intermetallic nanocrystals with enhanced catalytic properties for various applications is presented.